2020
DOI: 10.3389/fbioe.2020.00016
|View full text |Cite
|
Sign up to set email alerts
|

A Method for Producing Highly Pure Magnetosomes in Large Quantity for Medical Applications Using Magnetospirillum gryphiswaldense MSR-1 Magnetotactic Bacteria Amplified in Minimal Growth Media

Abstract: We report the synthesis in large quantity of highly pure magnetosomes for medical applications. For that, magnetosomes are produced by MSR-1 Magnetospirillum gryphiswaldense magnetotactic bacteria using minimal growth media devoid of uncharacterized and toxic products prohibited by pharmaceutical regulation, i.e., yeast extract, heavy metals different from iron, and carcinogenic, mutagenic and reprotoxic agents. This method follows two steps, during which bacteria are first pre-amplified without producing magn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 43 publications
(66 reference statements)
0
43
0
Order By: Relevance
“…There is a great need to obtain large scale production of pure magnetosomes with lowest possible amount of such impurities or toxic components (other metals than iron). Therefore, Berny et al [22], developed a minimal growth medium for magnetosomes production with less or devoid of toxic components, and having similar magnetosome properties as those obtained in the best reported growth conditions by Zhang et al [17]. Firstly, magnetotactic bacteria were amplified in pre-growth medium [containing sodium lactate (2.6 g), NH 4 Cl (0.4 g), MgSO 4 •7H 2 O (0.1 g), K 2 HPO 4 (0.1 g), thiamin HCl (40 µg), ME6 (0.5 mL)] without producing magnetosomes [22].…”
Section: Nutrient-balanced Feedingmentioning
confidence: 99%
See 2 more Smart Citations
“…There is a great need to obtain large scale production of pure magnetosomes with lowest possible amount of such impurities or toxic components (other metals than iron). Therefore, Berny et al [22], developed a minimal growth medium for magnetosomes production with less or devoid of toxic components, and having similar magnetosome properties as those obtained in the best reported growth conditions by Zhang et al [17]. Firstly, magnetotactic bacteria were amplified in pre-growth medium [containing sodium lactate (2.6 g), NH 4 Cl (0.4 g), MgSO 4 •7H 2 O (0.1 g), K 2 HPO 4 (0.1 g), thiamin HCl (40 µg), ME6 (0.5 mL)] without producing magnetosomes [22].…”
Section: Nutrient-balanced Feedingmentioning
confidence: 99%
“…Therefore, Berny et al [22], developed a minimal growth medium for magnetosomes production with less or devoid of toxic components, and having similar magnetosome properties as those obtained in the best reported growth conditions by Zhang et al [17]. Firstly, magnetotactic bacteria were amplified in pre-growth medium [containing sodium lactate (2.6 g), NH 4 Cl (0.4 g), MgSO 4 •7H 2 O (0.1 g), K 2 HPO 4 (0.1 g), thiamin HCl (40 µg), ME6 (0.5 mL)] without producing magnetosomes [22]. In second step, magnetotactic bacteria were then fed with an iron rich fed-batch medium containing [sodium lactate (1.3 g), NH 4 Cl (0.2 g), MgSO 4 •7H 2 O (0.03 g), K 2 HPO 4 (0.03 g), thiamin HCl (27 µg), of ME6 (0.08 mL)] to allow magnetosome synthesis [22].…”
Section: Nutrient-balanced Feedingmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, it was shown that MSR-1 could be amplified with a good yield, i.e., the production of 10 mg of magnetosomes per liter of growth medium, by using a reduced growth medium that is devoid of chemicals of animal/cell origin, such as peptone and yeast extract, which are often used to promote bacterial growth, and of toxic substances, such as CMR (carcinogenic, mutagenic, reprotoxic) products and heavy metals. It yielded pure iron oxide nanoparticles, using a production method that abides by pharmaceutical production standards [7]. , species of magnetotactic bacteria belonging to Alphaproteobacteria that can be amplified in specific growth media (dark apple green background), species of magnetotactic bacteria belonging to Alphaproteobacteria that can be amplified in specific growth media and can produce more than 10 mg of magnetosomes per liter of growth medium (yellow green background), MSR-1 specie belonging to Alphaproteobacteria that can be amplified in specific growth media, can produce more than 10 mg of magnetosomes per liter of growth medium, and can be amplified in minimal growth media not containing peptone, yeast extract, toxic CMR products, and heavy metals.…”
Section: Preparation and In Vivo Anti-tumor Assessment Of Magnetosomesmentioning
confidence: 99%
“…By naturally synthesizing metallic NP, toxic products can be avoided and the environment can be respected since biological substances that are necessary for such synthesis are either used in limited quantity, e.g., for plants, or can be grown/amplified almost indefinitely without requiring a lot of natural resources, as it is the case for bacteria. In addition, living organisms, such as magnetotactic bacteria, may minimize variations in NP properties by using their own metabolism to produce NP, which might, to some extent, prevent the impact of environmental changes on NP properties [7].…”
Section: Introductionmentioning
confidence: 99%